Le Kenya en marche, 2000-2020 - Fouéré, Marie-Aude; Pommerolle, Marie-Emmanuelle; Thibon, Christian (Africae Studies, 2020)
This edited volume offers a broad understanding and particular visions of Kenya in the first quarter of the twenty-first century. By bringing together rigorous yet accessible contributions, it shows how, since the 2002 transition, Kenya has been striving for change through economic modernisation and political liberalisation. The planned transformations are coming to fruition, even if the legacies of the past and political habits are slowing down the process. The various chapters take us from developmental capitalism to extreme poverty and enduring inequalities, from reforms on paper to mixed results in multiple sectors: decentralised governance, natural resources, land, and education. They also explore Kenya's ancient and colonial history and the diversity of its population. Thus, the book helps understand contemporary political, religious and community cleavages, the asymmetries between towns and the countryside, between Nairobi and the coast, in a country open to the world, as much through trade and finance as through art networks.